Development of Virtual Reality-Based Ethno-SDGs Learning Media on Colloid Material to Improve Students' Chemical Literacy - Ladjidji, Delfris Ariya Pratama; Sudarmin, Sudarmin; Kurniawan, Cepi; Ramadhani, Dimas Gilang; Yulianto, Agung Ade; Massora, Kris; Widastra, Holifiled (International Journal of Active Learning, 2024)
This research aims to develop Ethno-SDGs-based learning media integrated with Virtual Reality (VR) technology on the colloid material to improve students' chemical literacy. This media integrates the local wisdom of Palu, such as Kaledo, Kapurung, Palumara, and Utadada, with the chemical concept of colloids. The background of this research is the low chemical literacy of students due to the lack of connection between learning and local contexts and technological innovations. The focus of this research is the development of contextually relevant and technology-based learning media. The research employs a Research and Development (R&D) method with the 4D model (Define, Design, Develop, Disseminate). Data were collected through expert validation of media and content, peer reviews, small-scale trial questionnaires, and pretest and posttest assessments. Expert validation indicated the media's feasibility, with scores of 80% for content aspects and 79% for media aspects, both within the acceptable range. Peer reviews resulted in an approval score of 82% for both content and media aspects. The student responses from the small-scale trial showed a satisfaction rate of 92%, categorized as very feasible. Students also indicated that the media was engaging and helped increase their motivation to learn. The N-Gain test results showed an improvement in chemical literacy skills after using this media. The research concludes that the Ethno-SDGs-based learning media integrated with VR is effective in enhancing students' chemical literacy.